Perception and Attitudes of Teachers about Counseling - Can, G.; Demir Güdül, Meryem (My University, 2011)
Contemporary education systems aim at not only cognitive development but also social, psychological and physical development of students. And this holistic development is only possible with the implementation of effective counseling and guidance services at schools. In this context, teachers are required to be voluntarily involved in school guidance services and to support these services. Reaching to the expected outcomes is impossible without teachers’ support and participation. In other words, making contributions to school guidance services depends on the nature of teachers’ perception and attitudes. Not being able to develop efficient guidance understanding means not knowing fundamental concepts and principles of guidance. At the same time, teachers with negative attitudes toward guidance services could not provide guidance services despite their aspirations. In this framework, investigating the guidance perception and attitudes of teachers who are critical elements of school guidance team is very important before starting guidance services at school. Thus, this research was carried out with 739 teachers (with guidance responsibilities) working at 33 primary schools and 9 secondary schools in Eskisehir, Turkey. Data about participants’ counseling perceptions was collected by means of Guidance Understanding Inventory (Öztemel, 2000) and data related with participants’ attitudes toward guidance was collected by Teacher Counselling and Guidance Attitude Inventory (Demir, 2010). As a result, it was found that guidance perception and attitudes of the teachers responsible for guidance services at classes were significantly high, there is a mediocre relationship (r=.43) between guidance perception and attitudes of the teachers. The results of the one way MANOVA analysis indicated that guidance perception levels and attitudes of participants about guidance differ significantly in some respects.
Keywords: counseling attitude; counseling perception